Women, culture, and politics in Latin America - Bergmann, Emilie L., 1949- (University of California Press, 1990)
The result of a collaboration among eight women scholars, this collection examines the history of women's participation in literary, journalistic, educational, and political activity in Latin American history, with special attention to the first half of this century.